Intrinsic magnetic refrigeration of a single electron transistor - Ciccarelli, C.; Campion, R.P.; Gallagher, B.L.; Ferguson, A.J. (American Institute of Physics, 2016)
In this work, we show that aluminium doped with low concentrations of magnetic impurities can be used to fabricate quantum devices with intrinsic cooling capabilities. We fabricate single electron transistors made of aluminium doped with 2% Mn by using a standard multi angle evaporation technique and show that the quantity of metal used to fabricate the devices generates enough cooling power to achieve a drop of 160 mK in the electron temperature at the base temperature of our cryostat (300 mK). The cooling mechanism is based on the magneto-caloric effect from the diluted Mn moments.